A century of Morita therapy: What has and has not changed. (10th April 2022) - Nakamura, Mitsuhiro; Niimura, Hidehito; Kitanishi, Kenji
Abstract: We review the history of Morita therapy (MT), which has existed for over 100 years, and examine what has changed over that period and what has not. Classic MT, which was dependent on a highly strict therapeutic approach, gradually lost its pre‐eminence, but at the same time, the fundamental theory of MT was refined. This theory came to be applied to current outpatient MT and adapted to inpatient MT. As MT was refined, a standard training system for therapists was established, adaptations to modern conditions were made and expanded, and comparisons to and dialogs with other psychotherapeutic concepts such as mindfulness became possible. To better evaluate MT, further work should be conducted on its effectiveness of from a clinical epidemiological perspective.